Episodic Future Thinking Reduces Reward Delay Discounting through an Enhancement of Prefrontal-Mediotemporal Interactions - Peters, Jan; Büchel, Christian (Neuron (Cambridge, Mass.), 2010)
Humans discount the value of future rewards over time. Here we show using functional magnetic resonance imaging (fMRI) and neural coupling analyses that episodic future thinking reduces the rate of delay discounting through a modulation of neural decision-making and episodic future thinking networks. In addition to a standard control condition, real subject-specific episodic event cues were presented during a delay discounting task. Spontaneous episodic imagery during cue processing predicted how much subjects changed their preferences toward more future-minded choice behavior. Neural valuation signals in the anterior cingulate cortex and functional coupling of this region with hippocampus and amygdala predicted the degree to which future thinking modulated individual preference functions. A second experiment replicated the behavioral effects and ruled out alternative explanations such as date-based processing and temporal focus. The present data reveal a mechanism through which neural decision-making and prospection networks can interact to generate future-minded choice behavior. ► Episodic imagery reduces impulsivity in intertemporal decision-making ► Adjustments in discounting were predicted by the degree of ACC-hippocampal coupling ► Decision-making and prospection networks interact to enable future-minded choice